The Integration and Development of Chinese and Western Sports Culture and Olympic Globalization - Ju, Li (ASEAN Journal of Sport for Development and Peace, 2025)
The purpose of this paper is to explore the uniqueness of Chinese and Western sports cultures and their integration and development in the context of globalization, especially in the Olympic Movement. Through a literature review, this paper analyzes the core features of the two sports cultures, the impact of globalization on sports culture, and the role of the Olympic Movement as a platform to promote cultural integration. In addition, the author examines the controversial points in the current research, and through deepening the comparative cultural research, the interaction mechanism between globalization and localization, the role of technology and social media, and sustainability and social responsibility, she proposes that the direction of future research should focus on deepening cultural understanding, promoting inclusive dialogues, and exploring the path of sustainable development of sports culture under the background of globalization, to maintain and enrich the diversity of human sports culture, emphasizing the importance of cross-cultural understanding and cooperation in promoting the pluralistic coexistence of global sports culture.